The perfect girl ebook A novel. - Macmillan, Gilly (2016)
The New York Times bestselling author of What She Knew returns with an electrifying new novel about how the past will always find us... "Literary suspense at its finest." —Mary Kubica, New York Times bestselling author of Pretty Baby "A wonderfully addictive book with virtuoso plotting and characters - for anyone who loved Girl on the Train, it's a must read." — Rosamund Lupton Zoe Maisey is a seventeen-year-old musical prodigy with a genius IQ. Three years ago, she was involved in a tragic incident that left three classmates dead. She served her time, and now her mother, Maria, is resolved to keep that devastating fact tucked far away from their new beginning, hiding the past even from her new husband and demanding Zoe do the same. Tonight Zoe is giving a recital that Maria has been planning for months. It needs to be the performance of her life. But instead, by the end of the evening, Maria is dead. In the aftermath, everyone—police, family, Zoe's former solicitor, and Zoe herself—tries to piece together what happened. But as Zoe knows all too well, the truth is rarely straightforward, and the closer we are to someone, the less we may see.